THE IMPACT OF INCLUSIVE LEADERSHIP ON ACHIEVING STRATEGIC COHESION-A SURVEY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES IN THE BAQUBAH MUNICIPALITY DIRECTORATE (World Economics and Finance Bulletin, 2025)
The research aims to shed light on the impact of inclusive leadership as an explanatory variable with its dimensions (openness, availability, readiness, and accessibility) on achieving strategic cohesion as a dependent variable with its dimensions (organizational arousal, organizational casting, and organizational synergy), within the work environment of the Baqubah Municipality Directorate. The research problem was represented by the following central question: (To what extent does inclusive leadership contribute to achieving strategic cohesion?) To answer the research question and achieve its objectives, the descriptive analytical approach was adopted to analyze the relationships between the variables and their dimensions, and to describe the phenomenon under study quantitatively and qualitatively through collecting, organizing, and analyzing data. The research community was represented by the individuals working in the Baqubah Municipality Directorate, numbering (950) employees in the Baqubah Municipality Directorate. A random sample of (261) respondents was selected. The questionnaire was used as the main tool for collecting data, in addition to benefiting from official records and direct observation. The data was analyzed and the researcher conducted descriptive tests, scale construction tests, and relationship and influence hypothesis tests to enhance the credibility of the results. The research reached a set of results, the most prominent of which was the presence of an impact of inclusive leadership in all its dimensions on strategic cohesion, as a result of which a set of recommendations was formulated that are hoped to benefit those concerned in the researched district .
Keywords: Leadership Inclusiveness; cohesion Strategic